Вы находитесь на странице: 1из 6

GENERALIZED

FUNCTIONS
M. I. VISHIK . .

. ..
The article is an intro-
duction to the theory of
,
generalized functions. The XX , -
strict definition of a -
generalized function is . ,
x ( -
given. The main attention ) -
is devoted to delta func- y, .
tion. Some examples of
, -
delta-shaped sequences . -
are considered. The deri-
vative of a generalized - (x x0): , -
, , x0 ,
function is defined. It is , -
proved that the derivative x, . ,
of the Heaviside function .

is the delta function. ,
.
fl -
- .. , . -
. .. -
. - -
fl
. (1937, . [5]). . , -
( -
- ), -
-. - .
-
(1950).
- -
. - , -
- (. [1, 2]).

. ,
fl , y = f (x) ,
- x, < x < +, -
-. y. -
, f (x) -
: 1) x,
, , xi , -
; 2) f (x) -
.., 1997

[a, b]: | f (x) | #

# M (a, b) a # b; M . -
y = f (x),
< x < +.

(x),
< x < + ( (x)

112 , 12, 1997

, l f 1 ( ), l f 2 ( ) (. [1, 2]). , -
[c, d]: (x) = 0 < l f 3 ( ) = l f 4 ( ) , C0 ,
< x # c d # x < +, c < d,
f3(x) = f4(x) x, , ,
c d (x)).
f3(x) f4(x).
(x)
C0 ((x) C0). f (x) , y = f(x) -
, (x) C0 , -
: lf () (1)
(x) C0 ,
+
(1) (x) C0 .
f ( x ) ( x ) dx l ( ). f
(1)

. -
- -
, (x) = 0 . l(),
, (x) C0 - C0 , , (2) (3):
(1) (
lf ()), l(c11 + c22) = c1l(1) + c2l(2),
f (x) (x). l(),
(x) C0 - c1 , c2 R, 1 , 2 C0 (4)
l(), . , - ( ),
lf (), (1), -
C0 . lf () (1) l(n) l(), n(x) (x) C0 (5)
.
( ).
, lf ()
(1) : l()
, -
+
(1).
l f ( c1 1 + c2 2 ) = f ( x ) ( c ( x ) + c ( x ) ) dx =
1 1 2 2 , -
(1). ,
+ + , l(),
= c1 f ( x ) 1 ( x ) d x + c 2 f ( x ) ( x ) dx =
2

l() = (0) (x) C0 . (6)
= c1 l f ( 1 ) + c2 l f ( 2 ) (2)
,
1 , 2 C0 , c1 , c2 R. lf () (4), (5). (4)
- (6), , :
C0 :
l(c11 + c22) = c11(0) + c22(0) = c1l(1) + c2l(2).
n(x) (x) C0 ,
lf (n) lf (), n +. (3) (5) l()
(6) : n(x) (x), n +,
n(x) (x) C0 , - C0 , , , n(0) (0) n +.
: ) n(x), n = 1, 2, , - ,
[A, B],
n; ) {n(x)} x (x) ( l(n) = n(0) (0) = l().
> 0 N = N(), | n(x) , l() = (0)
(x) | < n \$ N < x < +). .
(.[3]), lf (), (1), - -
(3) . () (x), (x):
l(), (2)
(3), (0) = l() = () = (x), (x) (x) C0 . (7)
. , , , -
, (1) , -
lf () C0 , (x) C0 (0), ,

f(x). , f1(x), f2(x), - (x), (x) = (0). (8)
x0 ,
, - , -.

.. 113
(7) (8) -- +
n 1n
l()
f n ( x ) ( x ) d x = --- ( x ) d x =
2
: 1 n

= --- ( c n ) --- --- = ( c n ),

n 1 1 1 1
l() = l, = l(x), (x). (9) --- < c n < --- . (14)
2 n n n n
l()
l l(x). n + cn 0 -
(x) ((x) C0)
(cn) (0) n + (cn 0). (15)
(14) (15)
{ln} ( {ln()}). -
, 1n
l,
(x) C0 ln() l()
f n, = f n ( x ) ( x ) d x = ( c n )
1 n
ln , l, n +. -
( 0 ) = , (16)
l , -
, || # 0 , 0 n +. -
l0 , l() l0() 0 - :
C0 .
fn(x) (x) n +,

-
- (16).
l f n ( ) , - 2 .
n + -.
1 . fn(x), n = 1, 2, ,
1
, f ( x ) = --- ---------------
-, < x < + , 0 < < 0 . (17)
x2 + 2
n 1 1
--- --- # x # --- , ( f(x)
2 n n > 0.)
f n( x) = (10)
1
0 x > --- . ,
n
, f(x) (x) +0, (18)

fn(x) 0 n + x 0, (11) (x) C0

+
+0
f ( x ) ( x ) dx
fn(0) + n +. (12) ( 0 ) = ( x ), ( x ) .

,
+ 1n
, 0 < < 1, A > 0.
--- d x = --- --- --- = 1.
n n 1 1
f n ( x ) dx = 2 2 n n
(13) +
1 n
f ( x ) ( x ) dx =

, -
l f n ( ) = f n, , A A +

= --- ---------------
1
(1), - , : + + x 2 + 2
- ( x ) d x. (19)
A

A

+

f n, = f n ( x ) ( x ) d x ( 0 ) = , .
,

+ +
- 1 1
,
---
x +
2
-2 ( x ) d x # max ( x ) ---
---------------
< x < + ---------------
x +
2
- d x . (20)
2

(. [3]) A A

114 , 12, 1997

+ A
1 1
x
-- = y, d x = dy

max ( x ) = ,
< x < +
lim ---
+0 f ( x ) ( x ) d x = lim ---
+0 x +
2
-2 ( x ) d x +
---------------

, (20)

A +
1 1
1
2 +
1 1
+ lim ---
+0 2

-2 ( x ) d x + lim ---
---------------
+0 ---------------
x +
2
- ( x ) dx =
2

+
--- ----2 - dy = --- arctg y
------------- =
x +
y
2
+ 1 A
1 A A
1
A
= 0 + ( 0 ) + 0 = ( 0 ) = ( x ), ( x ) .

= --- --- arctg ---------
1 A
- 0 +0. (21)
2
1
, f(x), (17), -
+0 -
, (18).
, 3. -
, t:
1
( arctg y )' = --------------2 . x
2
1+y 1 ----4t-
f t ( x ) = ------------e , t > 0, < x < + . (25)
2 t
,
(19) ( ft(x) -

t.) , ft(x),
A
1 (25), (11)(13)
---
x +
2
-2 ( x ) d x
--------------- 0 +0. (22) n t n + t +0.
, ,
2, ,
(19)
ft(x) (x) t +0. (26)

A A
1 1
---
x
2
+
-2 ( x ) d x = --- ( c )
---------------
---------------
x
2
+
-2 d x = ,
(x) C0

A A
2
+ ----
x
-
1
e ( x ) dx ( 0 ) = ( x ), ( x )
1 4t
A ------------
1 1
= --- ( c )
--------------2 dy =
1 + y
2 t

1
A
t +0.
, (26)
= --- ( c ) arctg ---------
1 A A +0
- arctg ---------
-

1

1 . -
, x, -

--- ( 0 ) --- --- = ( 0 ) = ( x ), ( x ) . (23)
+0 1 -
2 2 . , (
x = 0) t = 0 -
(23) - ,
- t = 0 T = T(0, x)
, 0 (t = 0, t ). ,
[4], t > 0
A < c < A, , c 0 x T = T(t, x)
(25):
+0. (24) x
2

1 ----4t-
T ( t, x ) = ------------e = f t ( x ) (. [4]).
, , 2 t
x
-- = y, d x = dy .
( , -
. .) (26)
, (24) c 0 +0, ,
, (c) (0) +0. t +0 T(t, x) = ft(x)
-.
(19), (21)(23) , ,

.. 115
, l(0)
x = 0 . 1
l1() C 0 (l1() -
C 0 ), C 0 ,
1 1

l1() = l(') C 0 .
1
(28)
, -
: l1() =
, - = l', , l(') = l, ', (28) -
. - :
,
l', = l, ' C 0 .
1
, (29)
.
-
,
(27), -
-
:
, -
. f ', = f, '.
f(x) (x) - -
f '(x) '(x) , -
< x < +. , , (27):
(x) -
(a, b), < x # a b # x < +, +
b > a. , -
,
g ( x ) h ( x ) dx = g, h .

+ b
, :
f ' ( x ) ( x ) dx = f ' ( x ) ( x ) dx = l'
a l,
b + (29), -

= f ( x ) ( x ) a f ( x )' ( x ) d x = f ( x )' ( x ) dx, (27)
b
(27).
a 4. -.
(x) = 0 x = a x = b. (29) l' = '(x)
, (x) 0 x # a (x) 0 l = (x)
x \$ b. (27) -
(x) '(x), (x) = (x), '(x) = '(0).
. , - (
1 ) -
C -
0
, C 0
1
(x), < x < +,
'(x), < x < +, - -
(x) . , '(x)
- , (x) -
(x) (, 1
C 0 ,
). : l1() - . , -, '(0) -
1
C 0 . , - , -, ', n = n' ( 0 ) '(0) = ', ,
, l1() (4) - n(x) (x) C 0 , '(x)
1

l1() C 0 (5)
1
1
C 0 .
l1() C . , n(x)
1
0 5. .
(x) C 0 l1(n)
1
l1(). (x)
n(x) (x) C 0 , n(x) (x) C0
1
, :
'n ( x ) ' ( x ) C0 . , l1() - (x) = 0 x < 0, (x) = 1 x \$ 0.
1
C 0 .
, x0 = 0.
- '(x) x 0 -
l(0) C0 (l(0) C0), : '(x) = 0 x 0. x = 0 (x)
0 C0. . (x)

116 , 12, 1997

, , - , -
, ,
[1, 2].
+ +

( ) = , = ( x ) ( x ) d x = ( x ) dx
0

( x ) C 0 . 1. .., ..
. .: , 1958. 439 .
'() ()
. , 2. .. . -
. .: , 1965. 327 .
(29), C 0
1

3. .. -
+ . .: , 1955. 440 .
', = , ' = ( x )' ( x ) dx = 4. .., .. -
. .: , 1951. 659 .
+

' ( x ) dx = ( x )
+
= 0
= ( 0 ) = , (30) 5. .. -
. .: ,
0 1988. 333 .

( -
, * * *
(x) 0 x). (30),
, --
'(x) = (x). , -
. .. ,
, - -
' - . 242
-, . .

.. 117